Stability conditions to Bresse systems with indefinite memory dissipation. Issue 6 (25th April 2020) - Fatori, Luci Harue; de Oliveira Alves, Michele; Fernández Sare, Hugo D.
ABSTRACT: We study the asymptotic behavior of Bresse system with non-dissipative kernel memory acting only in the equation of longitudinal displacement. We show that the exponential stability depends on conditions regarding the decay rate of the kernel and a new relationship between the coefficients of the system. Moreover, this new condition on the constants of the system is used to prove strong stability and exponential stability for the homogeneous case (frictional dissipation in the longitudinal equation).